A randomised controlled trial of amnioexchange for fetal gastroschisis. (20th May 2019) - Luton, D; Mitanchez, D; Winer, N; Muller, F; Gallot, D; Perrotin, F; Jouannic, J‐M; Bretelle, F; de Lagausie, P; Ville, Y; Guibourdenche, J; Oury, J‐F; et al.
Abstract : Objective: Morbidity in fetuses affected by gastroschisis is mainly the result of bowel ischaemic and inflammatory processes. Experimental studies on animal models show that clearing amniotic fluid from the digestive secretions by amnioexchange procedures reduces the inflammatory process. We evaluated the benefit of the amnioexchange procedure for fetal gastroschisis in humans. Design: Prospective, interventional, randomised study. Setting: Eight referral centres for fetal medicine. Population: Pregnant women carrying a fetus with gastroschisis. Methods: We compared, in utero, amnioexchange with a sham procedure. The protocol included, in both arms, steroid injections at 30 weeks of gestation and the use of postnatal minimal enteral feeding. Main outcome measures: The primary outcome was a composite variable based on the duration of ventilation and parenteral nutrition. Secondary outcomes were the effectiveness and safety of the amnioexchange procedure, including the rate of perinatal death, time to full enteral feeding, primary closure, and late feeding disorders. Results: Sixty‐four patients were randomised. There was no difference in the composite criteria between the amnioexchange and control groups. Based on an intention‐to‐treat analysis, there were no significant between‐group differences in pregnancy outcome or complications. When studying the relationship between digestive compounds and amniotic fluid inflammatory markers, a clear correlation was found between bile acid and both ferritin and interleukin 1β (IL1β). Conclusions: In humans, amnioexchange, as described in our protocol, is not an option for fetal care; however, we provide supplementary proof of the involvement of inflammation in the pathogenicity of gastroschisis and suggest that future research should aim at reducing inflammation. ClinicalTrials.gov: NCT00127946. Tweetable abstract: A prospective, interventional, randomised study shows no benefit of amnioexchange for fetal gastroschisis in humans. Tweetable abstract: A prospective, interventional, randomised study shows no benefit of amnioexchange for fetal gastroschisis in humans.